CONSUMER PREFERENCES TOWARDS SLOW FASHION PROCESS VALUE. CASE STUDY OF: X,Y,Z - Mardhiyah, Nabilah; Dellyana, Dina (Journal of Business and Management, 2018)
Abstract. The word of sustainable living had been trends nowadays, fashion consumers are shifting towards sustainable slow fashion step by step. Thus, Indonesian fashion brands need to have knowledge in understand consumer preferences towards slow fashion process value. The research was conducted to study consumer preferences on slow fashion process value. The research uses qualitative method with Analytic Hierarchy Process (AHP) analysis, and Microsoft Excel processing. The research will have experts judgment in doing the AHP process. According to research, consumer of slow fashion are preferring durability in designing process meaning that longevity of the clothes are the most valued weight, quality driven in production process meaning that not only the quality of the clothes itself but also the quality of surrounding such as workers welfare and environment, and waste management in consumption process meaning that designers should be handling their waste better by reuse, reduce, recycle, or cradle to cradle. The brand that are most preferable to consumers is Brand Z. Thus, the recommendation is addressed to slow fashion companies in Indonesia, this research should be use as process priority based on consumer preferences. Thus, the recommendation of this research is aimed to the Indonesian Fashion Brands who is starting the slow fashion cycle. This research could be a consideration to have a better priority in process planning based by consumer preferences.Keyword: : Fashion Industry, Indonesian Fashion Brands, Slow Fashion